2011
DOI: 10.1002/chir.21022
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic separation and spectroscopic characterization of the e/z isomers of acrivastine

Abstract: A reverse phase high performance liquid chromatography (HPLC) method has been developed for the separation of two geometric isomers of Acrivastine using crude reaction mixture. The resolution between two isomers was found more than 2.9. The geometric isomers have been isolated by preparative HPLC and characterized by spectroscopic techniques, such as NMR, infrared, and MS. The developed method has been validated for the determination of Z-isomer in Acrivastine. The limit of detection and limit of quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Compound 4 is a reported impurity of acrivastine, and the 1 H and 13 C NMR data (Supporting Information S1 and S2, Tables S1 and S2) agree well with the reported acrivastine Z ‐isomer [18]. To confirm the configuration of C11═C19, the planar structure of 4 is constructed by detailed analyses of 1 H NMR, 13 C NMR, 1 H 1 H COSY, HSQC, and NOESY (Supporting Information S15–S19).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Compound 4 is a reported impurity of acrivastine, and the 1 H and 13 C NMR data (Supporting Information S1 and S2, Tables S1 and S2) agree well with the reported acrivastine Z ‐isomer [18]. To confirm the configuration of C11═C19, the planar structure of 4 is constructed by detailed analyses of 1 H NMR, 13 C NMR, 1 H 1 H COSY, HSQC, and NOESY (Supporting Information S15–S19).…”
Section: Resultssupporting
confidence: 60%
“…Previous studies mainly focused on the quantitative determination of acrivastine in biosamples using spectroscopy [11], GC-MS [12], SPE-HPLC [13], HPLC-MS [14], and electrochemical methods [15]; the quantitative determination of acrivastine formulation using HPLC with monolithic stationary phase [16]; simultaneous analysis of acrivastine and pseudoephedrine hydrochloride by HPLC [16,17]. Recently, the Z-isomer of acrivastine has been isolated and structurally elucidated using HPLC [18]. Ajay Kumar et al [19] identified a process-related impurity, Imp-IV, and two oxidative degradation impurities, Imp-V and VI, using HPLC-MS, and the structures were confirmed by synthesis.…”
Section: Introductionmentioning
confidence: 99%